Estrategia de apoyo emocional basada en la teoría de adaptación de roy en jóvenes amputados - Castro Castro, María De Los Ángeles (2026)
Amputation in youth impacts their body image, functionality, and emotional health, representing a complex adaptive challenge. Roy's Coping Theory offers a comprehensive framework to guide nursing interventions that promote resilience and well-being. This study proposes an emotional support strategy based on this theory, with potential to improve the quality of life of young amputees. Objective: To design an emotional support strategy based on Roy's adaptation theory that facilitates the comprehensive adaptation of young amputees. Materials and methods: A systematic review was conducted, using PRISMA methodology for the analysis of 15 relevant articles taken from the academic Google database, Scielo, PubMed, among others, published from 2019-2024 Results: It was evidenced that the empathic accompaniment of nursing staff and individualized care promote resilience, positive coping and integration of the new body image, highlighting the value of structured interventions such as therapeutic conversations, visualization exercises and strengthening of the family environment. Conclusions: The application of Roy's model allows a holistic and effective approach, favoring the emotional recovery of young amputees, promoting their empowerment and integral well - being.